SOME FEATURES OF CULT PARAPHERNALIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Religious beliefs in the territory of Kyrgyzstan have deep, ancient roots, with preserved relics serving as vital connections to the past and forming an integral part of the people’s spiritual and ideological culture. This article aims to explore the distinctive features of ritual attributes associated with shamanistic and magical-healing practices, drawing upon field research materials.
Keywords: beliefs, shamanism, “kyrgyzchylyk,” rituals, traditions, customs, cult, attributes.